Communication Strategies for Creating Sustainable Public Awareness on Agricultural Biotechnology - M.N. Reddy (Journal of Agricultural Extension Management, 2025)
INDIA's long term economic prospects depend heavily on the agricultural sector which contributes a quarter of the GDP and provides livelihood to two-thirds of the population. It is, therefore, imperative that highest priority is accorded to agriculture. The rural demand for manufactured goods and services is also dependent on the expansion of the agricultural economy. India achieved 7 per cent plus GDP growth during 1995-96 and 1996-97, essentially due to the robust performance of the agricultural sector. Thus, development of agriculture is key to eradicating poverty, ensuring food security, generating demand for industrial goods and promoting overall development